"I Came up Short on the Academic Ladder:": A Grounded Theory Study of Careerism in Academic Surgery - Isak, Ergest; Hegde, Yash D; Barrett, Meredith; Mazer, Laura M; Dimick, Justin B; Sandhu, Gurjit (Annals of surgery, 2023)
This study aims to explore the definition of career success in academic surgery. Career success in academic surgery is frequently defined as the achievement of a specific title, from full professor to department chair. This type of definition is convenient and established, but potentially incomplete. The business literature has a more nuanced view of the relationship between titles and success, but this relationship has not been studied in medicine. Semi-structured interviews were conducted from May to November 2020. Data were analyzed in an iterative fashion using grounded theory methodology to develop a conceptual model. We conducted 26 semi-structured interviews with practicing surgeons differing in years of experience; 12 (46%) participants were female, mean age 48. Participants included five chairs of surgery, six division chiefs, and seven past or current presidents of national societies. Four themes emerged on the importance of titles: Some study participant reported that (1) titles are a barometer of success; others argued that (2) titles are not a sufficient metric to define success; (3) titles are a means to an end; and (4) there is a desire to achieve the title of a respected mentor. As the definition of career success in academic surgery changes to encompass a broader range of interests and ambitions, the traditional markers of success must come into review. Academic surgeons see the value of titles, as a marker of success and as a means to achieving other goals, but overwhelmingly our interviewees felt that titles were a double-edged sword, and that a more inclusive definition of academic success was needed.